Females do not express learned helplessness like males do. - Dalla, Christina; Edgecomb, Carol; Whetstone, Abigail S; Shors, Tracey J (Neuropsychopharmacology, 2008)
Women are more likely than men to suffer from stress-related mental disorders, such as depression. In the present experiments, we identified sex differences in one of the most common animal models of depression, that of learned helplessness. Male and female rats were trained to escape a mild footshock each day for 7 days (controllable stress). Each rat was yoked to another rat that could not escape (uncontrollable stress), but was exposed to the same amount of shock. One day later, all stressed rats and unstressed controls were tested on a more difficult escape task in a different context. Most males exposed to uncontrollable stress did not learn to escape and were therefore helpless. In contrast, most females did learn to escape on the more difficult escape task, irrespective of whether they had been exposed to controllable or uncontrollable stress. The sex differences in helplessness behavior were not dependent on the presence of sex hormones in adulthood, because neither ovariectomy of females nor castration of males abolished them. The absence of helplessness in females was neither dependent on organizational effects of testosterone during the day of birth, because masculinized females did not express helplessness as adults. Thus, sex differences in helplessness behavior are independent of gonadal hormones in adulthood and testosterone exposure during perinatal development. Learned helplessness may not constitute a valid model for depressive behavior in women, at least as reflected by the response of female rats to operant conditioning procedures after stressful experience.
Keywords: Analysis of Variance; Androgens; Animals; Avoidance Learning; Behavior, Animal; Castration; Conditioning, Operant; Disease Models, Animal; Electroshock; Escape Reaction; Female; Helplessness, Learned; Male; Rats; Rats, Sprague-Dawley; Reaction Time; Reinforcement Schedule; Sex Characteristics; Stress, Psychological; Testosterone